Can Clinicians Use Dimensional Information to Make a Categorical Diagnosis of Paraphilic Disorders? An ICD-11 Field Study. Issue 9 (6th August 2021) - Keeley, Jared W.; Briken, Peer; Evans, Spencer C.; First, Michael B.; Klein, Verena; Krueger, Richard B.; Matsumoto, Chihiro; Fresán, Ana; Rebello, Tahilia J.; Robles, Rebeca; Sharan, Pratap; Reed, Geoffrey M.
ABSTRACT: Background: The diagnosis of paraphilic disorder is a complicated clinical judgment based on the integration of information from multiple dimensions to arrive at a categorical (present/absent) conclusion. The recent update of the guidelines for paraphilic disorders in ICD-11 presents an opportunity to investigate how mental health professionals use the diagnostic guidelines to arrive at a diagnosis which thereby can optimize the guidelines for clinical use. Aim: This study examined clinicians' ability to use the ICD-11 diagnostic guidelines for paraphilic disorders which contain multiple dimensions that must be simultaneously assessed to arrive at a diagnosis. Methods: The study investigated the ability of 1, 263 international clinicians to identify the dimensions of paraphilic disorder in the context of written case vignettes that varied on a single dimension only. Outcomes: Participants provided diagnoses for the case vignettes along with dimensional ratings of the degree of presence of five dimensions of paraphilic disorder (arousal, consent, action, distress, and risk). RESULTS: Across a series of analyses, clinicians demonstrated a clear ability to recognize and appropriately integrate the dimensions of paraphilic disorders; however, there was some evidence that clinicians may over-diagnose non-pathological cases. Clinical Translation: Clinicians would likely benefit from targeted training on the ICD-11 definition of paraphilic disorder and should be cautious of over-diagnosing. Strengths and Limitations: This study represents a large international sample of health professionals and is the first to examine clinicians' ability to apply the ICD-11 diagnostic guidelines for paraphilic disorders. Important limitations include not generalizing to all clinicians and acknowledging that results may be different in direct clinical interactions vs written case vignettes. CONCLUSION: These results indicate that clinicians appear capable of interpreting and implementing the diagnostic guidelines for paraphilic disorders in ICD-11.